Cinnamomum verum Bark Extract Mediated Green Synthesis of ZnO Nanoparticles and Their Antibacterial Potentiality - Mohammad Azam Ansari; Mahadevamurthy Murali; Daruka Prasad; Mohammad A. Alzohairy; Ahmad Almatroudi; Mohammad N. Alomary; Arakere Chunchegowda Udayashankar; Sudarshana Brijesh Singh; Sarah Mousa Maadi Asiri; Bagepalli Shivaram Ashwini; Hittanahallikoppal Gajendramurthy Gowtham; Nataraj Kalegowda; et al. (Biomolecules, 2020)
Cinnamomum verum plant extract mediated propellant chemistry route was used for the green synthesis of zinc oxide nanoparticles. Prepared samples were confirmed for their nano regime using advanced characterization techniques such as powder X-ray diffraction and microscopic techniques such as scanning electron microscopy and transmission electron microscopy. The energy band gap of the green synthesized zinc oxide (ZnO)-nanoparticles (NPs) were found between 3.25−3.28 eV. Fourier transmission infrared spectroscopy shows the presence of Zn-O bond within the wave number of 500 cm−1. SEM images show the specific agglomeration of particles which was also confirmed by TEM studies. The green synthesized ZnO-NPs inhibited the growth of Escherichia coli and Staphylococcus aureus with a minimum inhibitory concentration (MIC) of 125 µg mL−1 and 62.5 µg mL−1, respectively. The results indicate the prepared ZnO-NPs can be used as a potential antimicrobial agent against harmful pathogens.